40 UMP students enjoyed the open air iftar at MPK field - Siti Nurfarmy, Ibrahim (2019)
Forty Universiti Malaysia Pahang (UMP) students enjoyed a casual, open air iftar at the Kuantan Municipal Council (MPK) field 2 in Kuantan on May 16, 2019. It was their first time having a breaking of fast at the field, which was a popular spot among the locals during the month of Ramadan.